COMMUNITY NARRATIVES OF SOCIAL TRAUMA – A Case Study of a Sitio in Mindanao - Berliner, Peter; B. Radics, George; B. Pulmano, Nadia; Kjaerulf, Finn; A. Anasarias, Ernesto (Psyke & Logos, 2009)
The article addresses social trauma in a conflict-affected community in Pikit, North Cotabato, Mindanao, in the Philippines. Through an analysis of narratives and community practices the study intends to answer the following question: How did armed conflict (organized violence) and internal displacement impact on the community and how did the community respond? The analysis of the interviews from the study shows that three themes were frequently used to describe and explain the state of the social fabric, i.e. how well it was functioning or how disrupted it was; namely, significant events in the community’s history; responses to harassment; and actors and coping. It is shown that organized violence, war and recurrent forced displacement of communities produce responses that form a complex pattern of suffering (social trauma) and resilience (positive transformation). The interviews give a fuller understanding of how social trauma is constructed and sustained in communities impacted by organized violence. The study of peoples’ narratives provides us with knowledge on how trauma is experienced and understood by the impacted community. The study shows that responses to organised violence may foster locally based adaptive processes that help the community to recover and responses that may be detrimental to the community’s social support system. To understand these processes, not as dualistic but as interwoven as social tissue, it is necessary to study how local narratives present problems and hope of a better future.